Extracorporeal membrane oxygenation support in refractory perioperative anaphylactic shock to rocuronium: a report of two cases. (November 2019) - Carelli, Matheus; Seco, Michael; Forrest, Paul; Wilson, Michael K; Vallely, Michael P; Ramponi, Fabio
In recent years, extracorporeal membrane oxygenation has become increasingly common in the treatment of in-hospital cardiac arrest in non-cardiac surgery patients. This includes cardiac arrest secondary to perioperative anaphylactic shock refractory to standard advanced life support protocols, which is a rare but catastrophic event associated with significant mortality. Neuromuscular blocking drugs are most commonly implicated in perioperative anaphylaxis, with rocuronium playing a major role. In this article, we report two cases of young and otherwise fit and well patients who experienced a perioperative arrest secondary to rocuronium anaphylaxis before elective surgery; both patients did not respond to conventional advanced life support, but survived neurologically intact after institution of urgent veno-arterial extracorporeal membrane oxygenation.